MEMBUAT INOVASI BARU UNTUK MASYARAKAT MEMANFAATKAN NASI SISA YANG DI OLAH MENJADI GENDAR VARIAN RASA - Sarah Caesarani; Ayu Amelia Putri (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Empowerment of communities affected by covid-19 in the village carenang District carenang Serang Banten regency by optimizing the potential of the village. The purpose of this community service is to help the community in creating income in accordance with the ability and competence of the community so that they can be independent, develop and not always rely on government assistance by helping the community make new innovations for the community to utilize leftover rice into flavor variant gendar. The public needs to know how important it is to stay entrepreneurial in this time of pandemic. The stage of activities was designed during this one month which was preceded by coordination and communication activities with the village of Carenang. The intended preparation is the setting of the target of the activity, and the location of the activity. The results of this activity are very in accordance with what is expected, namely in the activities carried out can help the community make new innovations from leftover rice that is processed into a gendar flavor variant accompanied by us students kkm group 55